TRADISI MALAMANG DI DESA LIMAU PURUIK KECAMATAN V KOTA TIMUR PADANG KABUPATEN PARIAMAN PROVINSI SUMATERA BARAT - Septiyana, Ana; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Malamang tradition is a tradition of cooking lamang or lemang together or mutual cooperation to commemorate traditional ceremonies and religious ceremonies and is still carried out until now by the people of the province of West Sumatra, especially in District V Koto Timur, Limau Puruik village. The purpose of this research is 1) to find out what is the meaning of Malamang, 2) to find out the procedure of implementing the nighttime tradition, 3) to find out at any time the nighttime tradition, 4) to find out the benefits of the nightang tradition in the lamang for the people of Limau Puruik Village, V Koto Timur District Padang Pariaman Regency, West Sumatra Province, 5) To find out what values are contained in the nighttime tradition. Research uses qualitative research methods with descriptive analysis. The results of this study the nighttime tradition is still carried out by the Limau Puruik community, V Koto Timur District, Padang Pariaman Regency, West Sumatra Province. This tradition is also part of the entry of Islam in the West Sumatra Coast. This tradition is usually carried out in religious ceremonies such as commemorating the Maulid Nabi Muhamaad AS, welcoming the holy month of Ramadhan, welcoming Eid al-Fitr and Eid al-Adha, commemorating the death ceremony which is usually 40 days of death and this tradition is also held in the month of lamang on the month of Sa'ban.Keyword : Malamang Tradition , Limau Puruik Village